Peculiarities of the Sociolinguistic Approach in Advertising Discourse - Kholboboeva Aziza Sherboboevna (Periodica Journal, 2022)
Language is a very powerful tool in advertising and advertising language is unique in terms of usage. The aim of this paper, among others, is to discuss the essential pecularities of the sociolinguistic approach in advertising discource. Advertising language influences the consumer’s purchasing attitude.This function of advert has been said to be completely socially useful completely ethical and relatively free from semantic problem (Boulton, 1978:83).
Keywords: discource; semantic; been; completely